O direito fundamental social ao trabalho na atualidade - Becker, Luciana Rosa (2017)
The present dissertation comes to contribute with the study of Fundamental Right to Work. In order to carry out the present research, the method of dialectical approach and the methods of historical and bibliographic procedure were used concomitantly, usin g doctrines, books, and laws on the subject addressed. Firstly, it was observed that Brazil had several Constitutions throughout its history as an independent country and a lot. Constitutions have always pr ovided a space for fundamental rights. This space has been expanded with each new Constitution, in a growing process, of expansion and introduction of new fundamental rights, following the changes that have occurred in the world sc enario. In the Federal Constitution of 1988, work is one of the foundations of the Democratic State of Law (Article 1, IV), a fundamental right to benefits (Article 6), a foundation of the economic order (article 170, caput) and base Of the s ocial order (article 193). It was sought to verify whether fundamental rights, e specially those with a social content, with an emphasis on the right to work, find a possible and efficient constitutional protection in the so -called prohibition of s ocial retrogression. The generation of Decent Work was analyzed as the goal of the ILO in Brazil, which in 1999 formalized the concept of decent work in the face of the challenges imposed by economic globalization, summarizing its hi storical mission of promoting opportunities for citizens to have a good job, Exe rcised in conditions of freedom, equity a nd security and able to guarantee a di gnified life. Subsequently, we sought to study globalization and the consequent structural or technological unemployment, analyzing how new technologies and automation has affected the Right to Work. The close connection between the fundamental right to work and the principle of human dignity was identified. It was found that this is affected when it is not recognized and promotes the real value of that one. The promotion and realization of the right to work imp ly the aid to the compensation of social inequalities, in the exercise of freedom and equality real and effective and, consequently, in the enjoyment of a dignified life. However, it is not enough to recognize the value of the fundamental right to work, it must be made viable. With the objective of finding a possible solution to the question of how to ensure human dignity and ensure and guarantee access to the fundamental right to work, in view of the economic and social crisis that the country has faced, a s well as the effects of Globalization in a technological era, we studied issues such as flexibilization, public policies to generate work and income, given the current context of structural or technological unemployment, it is necessary to seek alternativ es to human work, as a form of social inclusion and effective dignity of human person.